Testing Techniques in the Evaluation of Severity of HIV-Associated Neuro-Cognitive Disorder in Children - Saida N. Saidkhodjaeva1, Yokutkhon N. Majidova2, Asal N. Abduvakhitova3, Umida U. Abdullaeva4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: The number of HIV infected children exceeds 3 million worldwide. The most severe clinicalmanifestations and complications of the disease are HIV-associated neurocognitive disorder and HIVencephalopathy. These factors make the scientists search for method of optimizationin the diagnosis ofneuro-HIV and identifying various pathological processes that determine the clinical course.Materials and Method: 154 children were tested with HIV diagnosis. All patients were examined forneurological, psychological and cognitive disorders. Quality of life of sick children were examined by thequestionnaire of PedsQL. In order to compare the results, study included 20 healthy adolescents (controlgroup - CG), who also tested using the above method. Using the MS Excel software average valuessummarized and their standard deviations were calculated.Results: All patients were diagnosed with 3rd and 4th stages of HIV. HIV-associated neurocognitive disorder:grade 2 in 100 patients – 64.94% and grade 3 - in 54 patients - 35.06%. Epilepsy was diagnosed in 31 patients,peripheral polyneuropathy in 7, vacuolar myelopathy in 8, and consequences of acute cerebrovascularaccident in 9 with focal neurological deficit in 2. The Raven test: average test result was 18.68±4.51%.Aggressive behavior: negativism prevailed in 74 patients, and in 11 cases (7.14%) it was combined withphysical aggression, and in 12 cases (7.79%) - with resentment. In addition, indirect aggression was detectedin 18 patients (11.69%), resentment in 41 patients (26.62%), suspiciousness in 10 patients (6.49%), and 19patients (12.34%) - irritation. Quality of life questionnaire revealed difficulties associated with physicalactivity (18.30±4.51 with maximum score of 32 points), with emotional states (15.50±2.23 with maximumof 20), social activity (14.10±2.93 with maximum of 20) and life in school (19.29±1.23 with maximumof 20).Conclusion: HIV-associated neurocognitive disorder is manifested by a deterioration in intelligence, variousforms of aggressive behavior and is associated with a decrease in the quality of life in terms of physical,emotional, social activity and learning at school.